Financial Feasibility Analysis of Hydroponic Vegetable Farming in Kendari City (Case Study of Simbo Hydroponics) - Sahra, Nureni; Iswandi, R. Marsuki; Sudarmo, Hadi (International journal of technology and education research, 2025)
This study aims to analyze the financial feasibility of vegetable farming with a hydroponic system in Kendari City, with a case study on Simbo Hydroponics. Simbo Hydroponics is a household business that utilizes the Nutrient Film Technique (NFT) system to cultivate several types of vegetables including lettuce, pak choy, Chinese cabbage, caisim cabbage, and samhong. This study uses a quantitative and qualitative approach with data collection techniques through observation, interviews, and documentation. The analysis includes calculating income, Revenue Cost Ratio (RCR), and Break Even Point (BEP). The results of the analysis show that the Simbo Hydroponics farming business has a positive income level and an RCR value > 1, which means that this business is financially feasible to be developed. The break-even point (BEP) of production and price also shows that the business is in a profitable condition. Thus, this hydroponic business can be used as an alternative urban agricultural business that is efficient, sustainable, and has bright prospects